BASIC LITERACY SKILLS THROUGH THE SCHOOL LITERACY MOVEMENT (GLS) AT SDN 6 PEKANBARU - Dewi; Antosa, Zariul (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
The School Literacy Movement (GLS) is a policy issued by the government to overcome the problem of education and improve the basic literacy abilities of students. SDN 6 Pekanbaru is one of the schools that has implemented GLS at the familiarization stage well. Therefore, this study aims to determine the basic literacy skills of students in low classes through the implementation of GLS in SDN 6 Pekanbaru. This study used qualitative research conducted through observation and interviews about the implementation of GLS and students’ basic literacy skills with teachers and students in classes I and II. The results showed that GLS was able to improve the phonetic abilities of students by achieving a very good level of the ability to read and pronounce combinations of letters. The increase of students' vocabulary comprehension ability was seen where most students were able to know the meaning of words and retell the contents of books with theme daily activities. From the research findings, it was concluded that GLS improved the basic literacy ability of low-class students at SDN 6 Pekanbaru.